Exploring the Nexus between Macroeconomic Variables and Stock Market Returns in Nepal: An ARDL Bounds Testing Approach - Shrestha, Purna Man; Rana, Mahesh (Journal of Business and Management, 2024)
Background: Investors and policymakers must understand how macroeconomic variables (MEVs) affect stock market behavior to maximize portfolios and maintain economic stability. Hence, it is crucial to establish a nexus between MEVs and stock market returns (SMRs). Objectives: This study seeks to assess the effects of MEV on SMRs in the long and short run. Methods: This paper analyzed the cointegrating relationship between MEVs and SMRs using a time series data set from 1994 to 2023. This study used the ARDL bounds testing approach. Results: The results confirm a cointegrating association between MEVs and SMRs in the Nepalese stock market. The error correction (ECT -1) term is significantly negative, suggesting a persistent correlation between the variables. The study also shows that interest rates negatively affect SMRs over time. Real GDP (LRGDP), inflation (LINFR), and exchange rate (LEXR) have negative but statistically insignificant associations with SMRs. However, the money supply (LMS) positively correlates with SMRs. Conclusion: The study’s findings provide practical advice for policymakers. For instance, lower interest rates increase the appeal of stocks by reducing the opportunity costs of holding bank deposits and credit costs. Therefore, policymakers are advised to maintain lower interest rates to cultivate a more appealing investment environment. Furthermore, policymakers should prioritize regulating inflation and preserving a robust foreign exchange rate to boost investors’ SMRs.